Paediatric spinal fusion surgery and the transition to home‐based care: provider expectations and carer experiences. (6th May 2013) - Barnard, Juliana G.; Albright, Karen; Morrato, Elaine H.; Nowels, Carolyn T.; Benefield, Elise M.; Hadley‐Miller, Nancy A.; Kempe, Allison; Erickson, Mark A.
Abstract There are more than 12 million children with special healthcare needs (CSHCNs) in the United States, many of whom require specialised health‐care to treat chronic physical and developmental conditions. This study is a qualitative investigation of programme, surgical and at‐home recovery experiences among CSHCNs and their family carers who participated in a spine surgical care programme at a paediatric hospital in the Western United States. The programme is designed to manage increased surgical risk and the transition of care from hospital to home for children with severe scoliosis undergoing spinal fusion surgery. We conducted 30 semi‐structured in‐depth interviews with 14 surgical team members and 16 family carers of children who had programme evaluations and spinal surgeries in 2006. Data were collected in 2008 and 2009 in hospital or at home locations to gather programme participation feedback from families and inform the adequacy of programme support to families during at‐home recovery. Data were analysed by reflexive team and content analysis methodologies. Results showed the programme was effective at improving preoperative surgical evaluation and helping families to anticipate some aspects of the surgical experience and hospital discharge. However, the impact of spinal fusion surgery and the subsequent transition to home‐based care was profoundly emotional for patients and their carers. Our data indicate that programme providers underestimated the extent of emotional trauma experienced by patients and families, particularly during the at‐home recovery process. The data also suggest meaningful differences in providers' and carers' expectations for surgery. Carers' disappointment with their recovery experiences and the perceived lack of post‐discharge support impacted their interpretations of and perspectives on their surgical experience. Implications of this research for surgical care programmes include the need for assessment and provision of support for physical, social, and emotional burdens experienced by patients and carers at pre‐surgical, surgical and at‐home recovery phases.